Peran Perempuan dalam Pengembangan Ekonomi Melalui Kegiatan UMKM di Kabupaten Bantul - Mutmainah, Nurfitri (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2020)
This study intends to explain and analyze the role of women in the activities of UMKM in Bantul Regency. In this research, the roles that women must play in economic activities will be identified through the development of UMKM businesses. In addition to explaining and analyzing the role of women, there will also be explored in greater depth the risks or obstacles that arise from economic development through the UMKM sector. The method used in this research is descriptive qualitative method with data collection techniques in the form of literature study, observation and in-depth interviews of a number of women who are UMKM’s in Bantul Regency. Based on the research conducted, it was obtained that the roles played by women in economic development activities through the UMKM sector were capital, production, distribution and marketing aspects. The role of capital is carried out by women through cooperative networks, cooperation and coordination through social group forums, production aspects are carried out personally based on business experience and opportunities, aspects of distribution and marketing are carried out in the area of ​​residence. The barriers to economic business development are influenced by: a dual role in which the burden of housewives on the domestic ground and lack of support from families; self development and support from the Regional Government which is still very minimal.